Antibiotics during childhood and development of appendicitis—a nationwide cohort study. Issue 1 (15th September 2020) - Antonsen, Jacob; Hansen, Susanne; Morgen, Camilla S.; Jess, Tine; Jorgensen, Lars N.; Allin, Kristine H.
Summary: Background: Appendicitis is a common disease with a lifespan risk of approximately 8%. The full range of specific causes for the disease remains elusive, but an aberrant microbiota have been identified as a potential risk factor. Aim: To investigate if use of antibiotics in a paediatric population increases the risk of appendicitis in childhood and adolescence Methods: We conducted a cohort study from 1 January 1995 to 31 December 2014. A total of 1 385 707 children (0‐19 years of age) including 7 406 397 antibiotic prescriptions and 11 861 cases of appendicitis were included. Primary outcome was appendicitis requiring appendectomy according to previous use of antibiotics. Appendicitis and appendectomy were identified from nationwide hospital records, and exposure to antibiotics was identified from nationwide prescription register. Rate ratios (RRs) with 95% confidence intervals were estimated from Poisson and logistic regression models. Results: Children who received at least one course of antibiotics were at increased risk of developing appendicitis compared to unexposed children (adjusted RR 1.72 [95% confidence interval 1.61‐1.85]), mean age of developing appendicitis was 9.8 years (SD 4.1 years). The RR of appendicitis increased by 1.04 (1.04‐1.04) per antibiotic course. A higher risk of appendicitis was observed in children exposed to antibiotics within the first 6 months of life (RR 1.46 [1.36‐1.56]) and children exposed to broad‐spectrum antibiotics (RR 1.33 [1.27‐1.39]). After adjustment for number of antibiotic courses, the association between early age of antibiotic exposure and risk of appendicitis and the association between exposure to broad‐spectrum antibiotics and the risk of appendicitis both disappeared. Conclusion: Children who receive antibiotics are at increased and dose‐dependent risk of appendicitis. The underlying mechanisms merit further investigation.